Effects of marital status on breast cancer survival by age, race, and hormone receptor status: A population‐based Study - Zhen Zhai (Cancer Medicine, 2019)
Abstract Introduction It remains unclear whether marital status could affect the breast cancer‐caused special survival (BCSS) of patients with breast cancer. Therefore, we sought to explore the influence of demographic and pathological factors on prognosis of patients with breast cancer. Materials and methods We selected patients meeting the eligibility criteria from the Surveillance, Epidemiology, and End Results (SEER) cancer registry program. We assessed the effect of marital status on overall survival (OS) and BCSS using Kaplan‐Meier curve and multivariate Cox proportional hazards regression. Results Compared with divorced/separated/widowed (DSW) patients, the married (AHR 0.7483, 95% CI: 0.729‐0.7682, P < 0.001) and single patients had better BCSS (AHR 0.9096, 95% CI: 0.8796‐0.9406, P < 0.001). Married patients kept better prognosis among all age subgroups, while the better BCSS of single patients occurred only in groups older than 35 years. As for race and hormone receptor status (HRs), the better BCSS of single patients was only observed in white race (AHR 0.881, 95% CI: 0.8457‐0.9177, P < 0.001) and patients with ER+/PR + status (AHR 0.8844, 95% CI: 0.8393‐0.932, P < 0.001). Conclusion Our findings demonstrated that married and single patients with breast cancer had better prognosis than their DSW counterparts. Age, race, and HRs could affect the correlation between marital status and BCSS.